Cytoreductive Surgery for Advanced Ovarian Cancer. (March 2014) - Pölcher, Martin; Zivanovic, Oliver; Chi, Dennis S
The amount of the largest diameter of visible residual tumor after cytoreductive surgery remains one of the strongest prognostic factors In advanced ovarian cancer. The Implementation of a more aggressive surgical approach to Increase the proportion of patients without visible residual tumor Is, therefore, a rational concept. Thus, the surgical management of advanced ovarian, primary peritoneal and fallopian tube cancers now Incorporates more comprehensive surgical procedures. However, these more extensive surgical procedures are associated with an Increased risk of morbidity, which may have a negative Impact on the oncologic outcome. In addition, It Is unclear whether all patients benefit from a comprehensive surgical Intervention In the same way or If there are patients whose disease course will not be Influenced by this approach. The methodologic analysis of surgical effectiveness Is complex and controversial owing to a lack of prospective surgical trials. This review acknowledges controversies and alms to discuss novel developments In the field of cytoreductive surgery for patients with ovarian, primary peritoneal and fallopian tube cancers. The focus of the review Is to discuss the role of surgery at Initial diagnosis. The role of secondary and tertiary surgery In the recurrent setting Is beyond the scope of this review.